Dense medium machine processing method for palm kernel/ shell separation - O.A. Ibrahim; C Uche; M Mahdi; C.A. Michael; G Sylvester (Journal of Applied Sciences and Environmental Management, 2018)
A machine processing method for the separation of cracked palm kernel from the shells using dense medium is presented. Cracked palm kernel is a mixture of kernels, broken shells, dusts and other impurities. In order to produce quality palm kernel oil, clean palm kernel nuts must be used, therefore the need for the separation of the palm kernel nuts from the shells. Several methods are used in the separation. The handpicking method yields good quality kernels but the method is slow, laborious and unsuitable for large scale productions. Salt solution method is unsuitable because of acidity of concentrated solution of salt used which affects the palm kernel as well as the quality of the oil produced. The clay suspension method is time consuming, laborious and cumbersome. The limitations of the above-stated methods of separation gave rise to the need for alternative methods of separation. A machine processing method using dense medium, a separator, a shell collector and a kernel collector was proposed. A machine was developed which produced kernels that contain 6.5% moisture content, 51% fat, 8.9% protein, 7% free fatty acid and 1.9% ash content. The kernels from the machine separation method were compared with the kernels produced by the other methods. The results revealed that the kernels obtained by hand picking method contains 7% moisture content, 52% fat, 9% protein, 7% free fatty acid and 2% ash content. The ones obtained using salt solution bath method contain 6% moisture content, 45% fat, 8% protein, 4.5% free fatty acid and 1.7% ash content. The ones obtained using conventional clay bath method contain 8% moisture content, 48% fat, 8.5% protein, 5.5% free fatty acid and 1.8% ash content. From the results obtained, the dense medium separation and clay suspension methods provide a better and cleaner means of palm kernel nut and shell separation because of the low moisture content and high fat, protein and ash contents among the methods of separation used.